2016
DOI: 10.1111/apa.13382
|View full text |Cite
|
Sign up to set email alerts
|

Using text messaging to obtain weekly data on infant feeding in a Danish birth cohort resulted in high participation rates

Abstract: Most mothers initiated breastfeeding, but only 1.1% were exclusively breastfeeding at 26 weeks. Text messaging resulted in high response rates and was a feasible data collection method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Out of the 48 studies, 40 were prospective cohort studies, 7 were RCTs and 1 was a longitudinal, quasi‐experimental study. Of the studies that focused on prelacteals, 20 focused on milk‐based prelacteals, 1 focused on water‐based prelacteals and 18 focused on prelacteals in any form (Agboado et al, 2010; Alikasifoglu et al, 2001; Balogun et al, 2016; Bruun et al, 2016; Cardoso et al, 2010; Chantry et al, 2014; Dashti et al, 2014; Demirci & Bogen, 2017; Dennis et al, 2014, 2019; Feinstein et al, 1986; Forster et al, 2006; Gray‐Donald et al, 1985; Hayek et al, 2019; Hossain et al, 1992, 1994; Hruschka et al, 2003; Lakati et al, 2010; McCoy & Heggie, 2020; McDonald et al, 2010; McKinney et al, 2016; Parry et al, 2013; Patil et al, 2015; Qiu et al, 2007, 2010; Raghavan et al, 2014; Raheem et al, 2014; Rasheed et al, 2009; Richard et al, 2021; Semenic et al, 2008; Sheehan et al, 2006, 1999; Tarrant et al, 2015; Vehling et al, 2018; Weisband et al, 2017; Zakarija‐Grkovic et al, 2016; Zarshenas et al, 2020) (Table 2). Of the studies that focused on the neonatal introduction of BMS, 7 focused on milk‐based BMS, 1 examined water‐based fluids and 2 examined BMS and/or water‐based fluids combined (i.e., any form) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 48 studies, 40 were prospective cohort studies, 7 were RCTs and 1 was a longitudinal, quasi‐experimental study. Of the studies that focused on prelacteals, 20 focused on milk‐based prelacteals, 1 focused on water‐based prelacteals and 18 focused on prelacteals in any form (Agboado et al, 2010; Alikasifoglu et al, 2001; Balogun et al, 2016; Bruun et al, 2016; Cardoso et al, 2010; Chantry et al, 2014; Dashti et al, 2014; Demirci & Bogen, 2017; Dennis et al, 2014, 2019; Feinstein et al, 1986; Forster et al, 2006; Gray‐Donald et al, 1985; Hayek et al, 2019; Hossain et al, 1992, 1994; Hruschka et al, 2003; Lakati et al, 2010; McCoy & Heggie, 2020; McDonald et al, 2010; McKinney et al, 2016; Parry et al, 2013; Patil et al, 2015; Qiu et al, 2007, 2010; Raghavan et al, 2014; Raheem et al, 2014; Rasheed et al, 2009; Richard et al, 2021; Semenic et al, 2008; Sheehan et al, 2006, 1999; Tarrant et al, 2015; Vehling et al, 2018; Weisband et al, 2017; Zakarija‐Grkovic et al, 2016; Zarshenas et al, 2020) (Table 2). Of the studies that focused on the neonatal introduction of BMS, 7 focused on milk‐based BMS, 1 examined water‐based fluids and 2 examined BMS and/or water‐based fluids combined (i.e., any form) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of breastfeeding in our cohort was relatively short when compared with current and study specific recommendations of 5-6 months of exclusive breastfeeding (Indenrigsministeriets helbredsudvalg, 1960). The proportion of infants that were breastfed for >4 months (19%) was about one third of that in a Danish cohort born in 2012 (70%; Bruun et al, 2016). Nevertheless, it was in the range of observed proportions among infants born in (32%) and out of wedlock (18%) in the Copenhagen Municipality in the years 1958-1962(Biering-Sørensen, Hilden, & Biering-Sørensen, 1980.…”
Section: Discussionmentioning
confidence: 98%
“…In general, breastfeeding provides health benefits for all infants [2], and specifically protects preterm infants from severe illness such as sepsis, necrotizing enterocolitis, and retinopathy of prematurity [3][4][5] and improve neurodevelopment [6]. Despite this, studies have shown that fewer preterm infants than term infants are breastfed exclusively at discharge; 45% of preterm infants in Sweden [7], 68% in Denmark [8] compared to 75% of 10-days-old term infants [9]. Countries outside of Scandinavia often have even lower exclusive breastfeeding rates at discharge; 55% of preterm infants in an Australian study [10], 23% in a Japanese study [11], and for very preterm infants 22% in an US study [12], and 20% in a European study of 11 countries [13].…”
Section: Introduction/backgroundmentioning
confidence: 99%